(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2021)
Among the ’writing’ testimonies that the APICE Centre at the University of Milan is committed to preserving, one is offered to us, with regard to Giovanni Giudici, not from the archive that bears his name, but from the fund called Biblíon (Biblioteca del Novecento), which has been part of APICE since the early days of its establishment: a fund that is mostly book-based and of which I will speak later on, but which also boasts an autograph by Giudici, a poem entitled Chi, which we will first transcribe.